2021
DOI: 10.1038/s41598-021-95487-5
|View full text |Cite
|
Sign up to set email alerts
|

Towards precision cardiometabolic prevention: results from a machine learning, semi-supervised clustering approach in the nationwide population-based ORISCAV-LUX 2 study

Abstract: Given the rapid increase in the incidence of cardiometabolic conditions, there is an urgent need for better approaches to prevent as many cases as possible and move from a one-size-fits-all approach to a precision cardiometabolic prevention strategy in the general population. We used data from ORISCAV-LUX 2, a nationwide, cross-sectional, population-based study. On the 1356 participants, we used a machine learning semi-supervised cluster method guided by body mass index (BMI) and glycated hemoglobin (HbA1c), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Characterising patient groups will allow defining new strategies for individual patients benefiting their needs to optimise health outcomes. Recent research, using profiling principles, found that healthcare for patients with cardiometabolic disease could benefit from more targeted and tailored strategies for the prevention of cardiometabolic diseases at a population level ( Fagherazzi et al, 2021 ). Eventually, post-acute treatment for BC survivors using a medication adherence enhancing eHealth technology can move from a “one-size-fits-all” vision to a tailored follow-up strategy, personalizing care to each BC survivor.…”
Section: Discussionmentioning
confidence: 99%
“…Characterising patient groups will allow defining new strategies for individual patients benefiting their needs to optimise health outcomes. Recent research, using profiling principles, found that healthcare for patients with cardiometabolic disease could benefit from more targeted and tailored strategies for the prevention of cardiometabolic diseases at a population level ( Fagherazzi et al, 2021 ). Eventually, post-acute treatment for BC survivors using a medication adherence enhancing eHealth technology can move from a “one-size-fits-all” vision to a tailored follow-up strategy, personalizing care to each BC survivor.…”
Section: Discussionmentioning
confidence: 99%
“…For example, individuals who have obesity, but do not demonstrate any comorbidities, have been subtyped as having "metabolically healthy obesity" [77]. Increasingly, more advanced methods-such as principal component analyses and machine learning based on anthropometric and clinical features-are being used for more refined subclassifications [78][79][80].…”
Section: Genetic Subtyping In Obesity and Metabolismmentioning
confidence: 99%
“…Fagherazzi et al 18 used various clinical, anthropometric, and laboratory factors to predict BMI and HbA 1c (a measure of average blood sugar levels over the past few months), and then applied a clustering approach to group individuals based on these predictions. The resulting clusters revealed important insights.…”
Section: Clinical Biomarkers For Identifying Obesity Subtypesmentioning
confidence: 99%